A Study on: Implementation of Legal Philosophy Values Information Regional Regulations in Indonesia: A Study on: Implementation of Legal Philosophy Values Information Regional Regulations in Indonesia - Gokma Toni Parlindungan S; Salamiah Muhd Kulal; Dorris Yadewani (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2026)
The purpose of this study is to analyze the application of legal philosophy values in the formation of regional regulations in Indonesia, as well as to examine the suitability between legal philosophy values and regional regulations that have been formed. This study uses a descriptive analytical research type with a normative legal approach method. Research data were obtained from primary, secondary and primary legal materials. Data collection techniques were carried out qualitatively. The results of the study indicate that the application of legal philosophy values in the formation of regional regulations in Indonesia is still not optimal. This is due to several factors, such as a lack of understanding of the values of legal philosophy among regional regulation makers, minimal community participation in the process of forming regional regulations, and weak law enforcement. This study has limitations in its focus on the application of legal philosophy values and a lack of analysis of the impact of regional regulations that do not follow these values.